An uncommon cause of recurrent pyogenic meningitis: pituitary abscess. (26th July 2010) - Walia, Rama; Bhansali, Anil; Dutta, Pinaki; Shanmugasundar, G; Mukherjee, Kanchan Kumar; Upreti, Vimal; Das, Ashim
Abstract : The authors report a 36-year-old male who presented with headache and hypopituitarism, and MRI revealed a ring enhancing lesion with pituitary stalk thickening. During follow-up, he presented with recurrent pyogenic meningitis with persistence of the lesion, therefore a diagnosis of pituitary abscess was considered. He underwent trans-sphenoidal surgery (TSS) with evacuation of pus and received antibiotic treatment for the same. After this he remarkably improved and had no recurrence of symptoms. He is on levothyroxine, glucocorticoids and testosterone replacement therapy for his respective hormone deficits.